(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Engaging students in Uzbek literature classes requires innovative and interactive teaching methods that stimulate interest and foster deeper understanding. This paper examines effective strategies for captivating students’ attention in literature classes, including the use of multimedia resources, interactive discussions, and creative assignments. Emphasis is placed on incorporating cultural and historical contexts to enhance relevance and connection with the material. By applying these strategies, educators can improve students’ engagement and comprehension, making literature classes more dynamic and impactful. The discussion aims to provide practical insights for teachers seeking to enrich their approach to teaching Uzbek literature.